2004
DOI: 10.1093/humrep/deh461
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ovarian histology in the management of patients presenting a premature ovarian failure

Abstract: Ovarian histology appears to be a reliable tool in evaluating the follicular reserve, and helpful and complementary to clinical and hormonal phenotyping in orienting the search for the various genetic causes of POF syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 21 publications
4
49
0
5
Order By: Relevance
“…We previously demonstrated that AMH levels in POF patients could identify women with persistent small follicles (35), but the value of serum AMH monitoring in POF has to be further evaluated in prospective studies. Unlike other authors (36, 37), we concluded, on the basis of our previous and current studies, that ovarian histology appears to be a more reliable tool in evaluating the follicular reserve (20). Indeed, the comparison of follicular pattern at pelvic ultrasonography and at ovarian biopsy confirms our previous data (20).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We previously demonstrated that AMH levels in POF patients could identify women with persistent small follicles (35), but the value of serum AMH monitoring in POF has to be further evaluated in prospective studies. Unlike other authors (36, 37), we concluded, on the basis of our previous and current studies, that ovarian histology appears to be a more reliable tool in evaluating the follicular reserve (20). Indeed, the comparison of follicular pattern at pelvic ultrasonography and at ovarian biopsy confirms our previous data (20).…”
Section: Discussionsupporting
confidence: 83%
“…Unlike other authors (36, 37), we concluded, on the basis of our previous and current studies, that ovarian histology appears to be a more reliable tool in evaluating the follicular reserve (20). Indeed, the comparison of follicular pattern at pelvic ultrasonography and at ovarian biopsy confirms our previous data (20). In 47 patients, images suggesting the presence of follicles were observed at ultrasonography.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Por outro lado, o papel da biópsia ovariana, no diagnóstico e prognóstico da FOP, é controverso e há relatos de gestações ocorridas em pacientes com biópsia negativa (22). A biópsia ovariana com ausência de folículo pode refletir apenas uma amostra inadequada de tecido, assim como a presença deles não implicar numa resposta positiva ao tratamento (44).…”
Section: Diagnósticounclassified